(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article emphasizes the transformative impact of integrating games and play-based activities for young learners in English language classrooms. It underscores how these methods promote holistic development by enhancing language skills, critical thinking, collaboration, and emotional growth. By involving children in interactive and enjoyable learning activities, educators establish dynamic environments that foster curiosity and creativity. These activities not only make language learning accessible and enjoyable but also provide opportunities for students to apply their skills in authentic contexts, reinforcing understanding and retention. Moreover, the text highlights the effectiveness of playful learning in building essential social competencies such as teamwork and effective communication, essential for future success. Overall, it advocates for an educational approach that leverages play to cultivate a positive attitude toward learning, preparing young learners to thrive academically and culturally in an interconnected world.